Platelet-Rich Fibrin (PRF) as an assistant in Oral Implantology: case report (Research, Society and Development, 2021)
Blood is an extremely important element for the healing process of injured tissues, this fact is due to the presence of numerous cells present in it, which are essential for the development of the physiological healing process. PRF is a second-generation platelet aggregate acquired through autologous blood centrifugation, which ends up reducing the acquisition of cross-transmissible infections, making this aggregate extremely safe. The PRF has been increasingly used within the dental surgical area, especially in third molar extraction procedures, installation of dental implants, lifting the maxillary sinus, alveolar cleft repair, preservation of the alveolar ridge after extraction, treatment of oral-sinusal communications. This paper aims to report a clinical case of installation of bone-integrated dental implants in which PRF was used to assist in the patient's postoperative period. A 58-year-old female smoker, hypertensive patient underwent surgery to install two Morse Cone implants in the lower left posterior region with subsequent use of PRF to assist in the postoperative period. After performing the clinical case reported, the effectiveness of the benefits of PRF mentioned in the literature was verified when used in surgeries for installation of dental implants.